Grewioideae Dippel (Malvaceae) in the state of Paraíba, Brazil - Souza, Stefanny Martins de (2020)
Malvaceae Juss. is included in the Malvales order and presents a cosmopolitan distribution. It comprises approximately 4,300 species allocated into 243 genera. The family is subdivided into nine subfamilies, amongst them Grewioideae with approximately 25 genera and 700 species associated to the tropical regions. In Brazil, this subfamily is represented by ten genera and about 60 species. The present work comprises the taxonomic survey of Grewioideae in the Paraíba State. Consultations were made to digitized databases as well as visits to physical herbaria, collecting expeditions and ‘in loco’ observations. Seven species from four genera were recorded in the study area: Apeiba tibourbou Aubl., Corchorus argutus Kunth, C. hirtus L., Luehea ochrophylla Mart., L. paniculata Mart., Triumfetta rhomboidea Jacq., and T. semitriloba Jacq.. The species Corchorus argutus is a new occurrence for the Paraíba State, occurring in an area of Caatinga.